Effects of Annealing on the Structural and Optical Properties of Silver Thin Films - O. Osanyinlusi; A.B. Alabi; K.A. Yusuf; M.M. Orosun (Journal of Applied Sciences and Environmental Management)
Silver thin films were prepared on glass substrates using chemical bath method. The thin films were annealed at different temperatures of 100 and 200oC for 1hour. The samples, as-prepared and annealed were  characterized using X-ray diffractometer (XRD) and Uv-Vis  spectrophotometer. XRD results revealed that silver films present a cubic phase with (111) preferred orientation. The XRD result and analysis also revealed that the intensity of the peaks and the crystallite size increase with increase in annealing temperature. All the films showed very low transmittance within the visible region with the 200oC annealed film having the highest at 1.4%. Reflectance was found to reduce from 65% for the as-deposited film to as low as 17% for the 200oC annealed film within the visible region of the wavelength. The reflectance reduces with increase in annealing temperature. The films also showed low percentage absorbance within the UV region of the wavelength with the 200oC annealed film having the highest absorbance of 2.79%.